The Improvement of the Relative Positioning Precision for GPS L1 Single Frequency Receiver Using the Weighted Smoothing Techniques - Byung-Kyu Choi; Jong-Uk Park; Jeong-Ho Joh; Hyung-Chul Lim; Phi-Ho Park (Journal of Astronomy and Space Sciences, 2004)
To improve the precision of relative positioning for GPS single frequency(L1) receiver, we accomplished the GPS data processing using the weighted smoothing techniques. The weighted phase smoothing technique is used to minimize the measurement error of pseudorange and position domain smoothing technique is adopted to make the complement of cycle-slip affection. we also considered some component errors like as ionospheric error, which are related with baseline length, and processed for several baselines (5, 10, 30, 40, and 150 km) to check the coverage area of this algorithm. This paper shows that weighted phase smoothing technique give more stable results after using this technique and the position domain smoothing technique can reduce the errors which are sensitive to the observational environment. Based on the results, we could find out that this algorithm is available for post-time and real-time applications and these techniques can be substitution methods which is able to get the high accuracy and precision without resolving the Integer ambiguity.